Length-weight relationship and condition factor of Stolephorus bataviensis from Mangalore area - Doddamani, M; Ramesh, T J; Shanbhogue, S L (Indian Journal of Fisheries, 2011)
The length-weight relationship and relative condition factor of 1,534 fishes ofStolephorus bataviensis (797 females and 737 males) were estimated from thesamples collected at Mangalore waters. The relationship for male was expressedby Log W = -1.036946 + 1.80955 Log L and for female, Log W = - 1.836013 +2.63931 Log L. The mean values of relative condition factor (Kn) varied between1.00172 and 1.01433 in male and 1.00292 and 1.01679 in female respectively